Amostragem de macroinvertebrados bentônicos: padronização da suficiência amostral - Benke, Cibelly Dayane (2013)
The aim was not to create a standardized regional sampling of aquatic macroinvertebrates, by drawing curves sampling sufficiency in streams with different types of diversity of these organisms. Were collected in nine streams of small order, in which 20 samples were collected, pooled and homogenized in a separate tray in 24 squares for analysis of sample sufficiency. 999 subsamples were taken randomly selected at random for each of the 23 squares on each stream analyzed. For each subsample data were taken from the total wealth of households (Ssub) and coefficient of correlation (r) between the abundances of total subsample (Asub) and sample (Aamo). Correlation analysis was used to verify that the quantities of squares determined for each stream were correlated with the Shannon diversity index. Qualitatively, it took an average of 16 squares to reach the criterion of sufficiency under sampled, while in quantitative terms, the sufficiency under sampled occurred on the seventh square. The positive relationship between diversity and subsampling of these organisms allows us to conclude that in environments where diversity is unknown, it will be necessary to draw up a "pilot study" for the use of this methodology. Thus, future work will find the number of subsamples required to be screened, as we prepared a table with the values of diversity and their respective values of sampling sufficiency (subsamples)